Kant and the early moderns - Garber, Daniel, 1949-; Longuenesse, Béatrice, 1950- (Princeton University Press, 2008)
For the past 200 years, Kant has acted as a lens--sometimes a distorting lens--between historians of philosophy and early modern intellectual history. Kant's writings about Descartes, Leibniz, Locke, Berkeley, and Hume have been so influential that it has often been difficult to see these predecessors on any terms but Kant's own. In Kant and the Early Moderns, Daniel Garber and Béatrice Longuenesse bring together some of the world's leading historians of philosophy to consider Kant in relation to these earlier thinkers. These original essays are grouped in pairs. A first essay discusses Kant's.